Does Discussion Lead to Opinion Change within Political Science Students? A Pedagogical Exercise of Deliberative Democracy. Issue 4 (2nd October 2021) - Archibugi, Daniele; Bavastrelli, Martina; Cellini, Marco
Abstract: While the model of deliberative democracy gives a crucial role to dialog, empirical evidence has not yet established if discussion helps to reach a better understanding of political issues and, above all, if individuals are prepared to change their views. It is still unclear when the deliberative model, and more specifically discussion, could be usefully employed as a teaching tool, to improve students' knowledge. This article presents an exercise performed within the Department of Political and Social Sciences at the LUISS University of Rome. Students were asked to discuss in the classroom the issues related to the course, and to cast a vote on selected issues before and after deliberation. Although our sample is not representative, we have gathered evidence from the same population on a rather large number of issues. Students changed their view in 24.6% of cases, and they agreed that discussion increased their understanding, while those with strong ex-ante views resulted more reluctant to change their opinions because of discussion. The analysis also showed the presence of individuals that are more likely to be permeable to discussion while others that are more likely to be impermeable.